ANALISIS PEMBERDAYAAN MASYARAKAT DI DESA WISATA KARANG BAJO - Moh Ari Rafandi; Sri Susanty; Agusman Agusman; Muharis Ali (Journal Of Responsible Tourism, 2023)
In this study, researchers used descriptive qualitative methods. The data collected in this study were sourced from the results of interviews, and documentation from parties related to community empowerment in the Karang Bajo tourist village. Researchers used data analysis, namely data reduction, data presentation, and drawing conclusions. Of all the data that has been processed and analyzed of course get the results of the research. Empowerment in the Karang Bajo tourist village that has been carried out includes capital assistance in the form of assistance to woven fabric craftsmen and assistance for renovating traditional houses. Assistance for infrastructure development in the form of the construction of the Sebaya Tanta heritage hall and traditional houses, repairing the road to Sebaya Tanta and the area around the ancient mosque. Mentoring assistance on traditional schools from the Directorate of Belief in God Almighty, assistance from the Alliance of Indigenous Peoples of the Archipelago and Santiri related to tourism from the perspective of indigenous peoples and waste management, assistance from students of the Mataram High School of Tourism Real Work Lecture related to tourism and leadership management. Institutional strengthening with the establishment of the Gubug Karang Bajo-Bayan Traditional Institution Institution, other community empowerment institutions such as Karang Taruna, PKK, and Pokdarwis. The partnership activity carried out is to establish partners between the indigenous people of Karang Bajo with the Alliance of Indigenous Peoples of the Archipelago and Santiri related to tourism and the lives of indigenous peoples.